Loss Minimisation by Optimal Reactive Power Dispatch Using Cuckoo Search Algorithm - M. H., Sulaiman; Muhammad Ikram, Mohd Rashid; Omar, Aliman; Mohd Rusllim, Mohamed; Abu Zaharin, Ahmad; Mohd. Shafie, Bakar (2014)
This paper presents a Swarm Intelligence (SI) technique namely Cuckoo Search Algorithm (CSA) which is inspired by parasitic behaviour of Cuckoo birds in reproduction strategy to obtain loss minimisation by solving the Optimal Reactive Power Dispatch (ORPD) problem. The proposed CSA is used to find the optimal combination of control variables such as generator voltages, tap changing transformers’ ratios and the value of reactive compensation devices in order to minimize the loss of the transmission system. To demonstrate the effectiveness of CSA, IEEE-57 bus system is used and compared to other techniques available in literature.